The “New Normality” and the Lessons of Stock-Market History - Nenkov, Dimiter (Research Papers, 2022)
The purpose of this paper is to explore the current situation on the stock-market and its price levels, against the background of historic stock-market bubbles. The study is developed in the context of the so called “new economy”, implying “new normality”, which has been widely used during the last more than two decades to justify the atypically high indexes and market multiples on the US stock-market. This concept does not originate from the tremors of the current Covid-19 pandemic, which has triggered the start of significant transformations in business environment. It is actually much older.The leading hypothesis of the study is that today’s US stock market is just in another price bubble, and no “new normality” factors could prove that it is fairly valued. With regard to this, a historic review is made of the major bubbles on the stock markets in the distant past and in the more recent past. The start, the development and the main features of these price bubbles are reviewed and analyzed. One of the tasks is to check whether the same features, as well as some erroneous visions from the past are not repeated in today’s market. Comparable indicators are used, such as the “price-earnings ratio” (PE). The study also addresses fundamentals, since they are supposed to dictate the true value of the stock market, and, at the same time, it is precisely these fundamentals that are mainly affected by the “new normality” views of the current stock market. The results indicate that the lessons of stock-market history have not been learnt as a whole, and the prerequisites for another bubble are in place nowadays.